Analysis of the concentration of gamma-emitting radioisotopes in marine fish samples - Maioli, Claudio; Mazzaglia, Stefania; Nan , Mahrail; Cioni, Federico (Progress in Nutrition, 2023)
Marine fish products (fish) represent an important source of nutrition for all mankind. In the food pyramid, fish products are located in the highest levels and therefore may absorb chemical pollutants and isotopes, thus transferring them to humans. The aim of the work was to verify the presence of gamma-emitting isotopes (131I, 137Cs, 210Pb) in a random sample consisting of 12 species of marine fish regularly caught in the oceans. The results demonstrate that there is no significant radioisotope pollution in the small sample analysed. However, the possible presence of isotopes in the marine environment should be monitored given that there are powerful nuclear weapons in the world and many ongoing conflicts